2020
DOI: 10.1186/s13567-020-00748-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung endothelial cells are sensitive to epsilon toxin from Clostridium perfringens

Abstract: The pore-forming protein epsilon toxin (Etx) from Clostridium perfringens produces acute perivascular edema affecting several organs, especially the brain and lungs. Despite the toxin evident effect on microvasculature and endothelial cells, the underlying molecular and cellular mechanisms remain obscure. Moreover, no Etx-sensitive endothelial cell model has been identified to date. Here, we characterize the mouse lung endothelial cell line 1G11 as an Etx-sensitive cell line and compare it with the well-charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…However, a humanized zebrafish model expressing human MAL in endothelial cells binds to ETX and responds by producing blood–brain barrier leakage, blood vessel stenosis, perivascular edema and blood stasis [ 157 ]. In mice, MAL expression was found in the endothelium of some lung vessels, supporting the hypothesis that MAL is a key element in the ETX-induced perivascular edema in the lungs [ 158 ]. ETX binding is clearly observed in the microvasculature of the central nervous system but not in the vasculature of peripheral organs in the mouse, indicating that ETX specifically targets the endothelial cells of the CNS.…”
Section: Mal and The Clostridial Epsilon Toxinsupporting
confidence: 60%
“…However, a humanized zebrafish model expressing human MAL in endothelial cells binds to ETX and responds by producing blood–brain barrier leakage, blood vessel stenosis, perivascular edema and blood stasis [ 157 ]. In mice, MAL expression was found in the endothelium of some lung vessels, supporting the hypothesis that MAL is a key element in the ETX-induced perivascular edema in the lungs [ 158 ]. ETX binding is clearly observed in the microvasculature of the central nervous system but not in the vasculature of peripheral organs in the mouse, indicating that ETX specifically targets the endothelial cells of the CNS.…”
Section: Mal and The Clostridial Epsilon Toxinsupporting
confidence: 60%
“…38 This bacterial species was equipped to produce the pore-forming protein epsilon toxin, which therefore alters intestinal permeability and enters the intestinal vascular system. 39,40 Herein, we also found that these three bacteria were significantly increased in colitis mice with lung injury, whereas BL-99 inhibited their growth in the intestine.…”
Section: Papermentioning
confidence: 57%
“…Several publications have demonstrated that knock out of MAL expression in pETX sensitive organisms or cell lines totally abolishes pETX binding and/or toxicity while exogenous expression of MAL confers pETX binding in normally resistant cells or organisms [ 62 , 97 , 98 , 126 129 ]. In addition, the specificity of pETX for MAL is supported by descriptive studies that strongly correlate pETX binding to MAL expression in multiple sensitive cell lines [ 130 132 ]. Finally, direct protein–protein interaction between pETX and MAL have been published by two independent groups via immunoprecipitation and affinity purification column [ 126 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…To detect EV MAL expression, we utilized binding of the MAL-specific ligand, pETX [ 98 , 126 ], as there is no currently available anti-MAL antibody suitable for flow cytometry. This ligand was selected based on numerous, independent studies that strongly indicate MAL is the receptor for pETX [ 62 , 97 , 98 , 126 132 ]. MAL has been repeatedly demonstrated by independent groups to be both necessary and sufficient for pETX binding [ 62 , 97 , 98 , 126 129 ].…”
Section: Discussionmentioning
confidence: 99%